The Automatic Recognition of Large Ball Valve Sealing Bolt Based on Digital Image - Song Qingjun; Xiao Xingming; Jiang Haiyan; Zhao Xieguang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this paper, we adopted the area filling method of the mathematical morphology to fill the holes of the nut. In addition, the bimodal method and multi-threshold method were combined for the image segmentation. Furthermore, the image edge was detected by mathematical morphology algorithm. Finally, the angle between the bolt and manipulator was calculated using the rotation conversion matrix. With the systematic error and correlation coefficient, the calculated angle was verified. Experimental results show that the method can protect the edge integrity of the nut image, with fast processing speed and strong anti-noise ability. The work in this paper provides a theoretical basis for the automatic recognition in the large ball valve sealing bolt system.